Earthworms regulate soil microbial and plant residues through decomposition - Jiahui Liao; Juanping Ni; Xiaoming Zou; Han Y.H. Chen; Manuel Delgado-Baquerizo; Yuanyuan Li; Tingting Ren; Ke Shi; Honghua Ruan (Geoderma)
Earthworms are keystone regulators of carbon exchange between terrestrial ecosystems and the atmosphere. However, exactly how earthworms regulate the composition of microbial and plant-derived carbon in soil organic matter remains poorly understood. Here we conducted a microcosm experiment with two species of endogeic earthworms (Drawida gisti and Metaphire guillelmi) to investigate their effects on cellular and extracellular-microbial residues versus fast and slow-decaying plant materials. We found that both species of earthworms reduced microbial residues (amino sugars or the protein content of extracellular polymeric substances (EPS)) and facilitated the decomposition of microbial residues rather than their formation. Neither earthworm species affected slow-decaying plant residues (lignin phenols). However, their effects on the fast-decaying fraction of plant residues (particulate organic matter (POM)) depended on the earthworm species. Principal component analysis (PCA) revealed that earthworms mediated two gradients between microbial and plant residues. The first gradient was between the nitrogenous fraction of microbial residues (e.g., amino sugars and EPS-protein) versus slow-decaying plant lignin, while the second gradient was between the fast-decaying POM versus EPS-polysaccharide. Our results suggest that earthworms play vital roles in mediating plant and microbial residue fractions in soil through their multifaceted mechanisms in regulating the chemical composition of organic carbon, and in understanding biological control of the global soil carbon cycle.